2001
DOI: 10.1086/321663
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Density and Power Spectrum from Peculiar Velocities: Nonlinear Corrections and Principal Component Analysis

Abstract: We allow for nonlinear e †ects in the likelihood analysis of galaxy peculiar velocities and obtain D35% lower values for the cosmological density parameter and for the amplitude of mass density ) m Ñuctuations This result is obtained under the assumption that the power spectrum in the linear p 8 ) m 0.6. regime is of the Ñat "CDM model (h \ 0.65, n \ 1, COBE normalized) with only as a free parameter. ) m Since the likelihood is driven by the nonlinear regime, we "" break ÏÏ the power spectrum at (h~1 k b D 0.2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 67 publications
4
41
0
Order By: Relevance
“…Those analyses also give the high mass fluctuation levels (σ 8 Ω 0.6 m ) around 0.8-1.1 (Table 3 and 4). On the contrary, Silberman et al (2001) found a power deficiency at k = 0.1 hMpc −1 from the ML analysis of the SFI sample, and their density PS and σ 8 Ω 0.6 m are consistent with our results. As shown in Figure 8, the β in the quasi-linear regime is more accurate than that in the linear-regime.…”
Section: Discussionsupporting
confidence: 90%
“…Those analyses also give the high mass fluctuation levels (σ 8 Ω 0.6 m ) around 0.8-1.1 (Table 3 and 4). On the contrary, Silberman et al (2001) found a power deficiency at k = 0.1 hMpc −1 from the ML analysis of the SFI sample, and their density PS and σ 8 Ω 0.6 m are consistent with our results. As shown in Figure 8, the β in the quasi-linear regime is more accurate than that in the linear-regime.…”
Section: Discussionsupporting
confidence: 90%
“…For h º 0.65, intersection of the velocity power spectrum and Lya P(k) constraints occurs at n [ 0.8, incompatible with the CMB anisotropy constraint. However, an universe would require a low value of ) m D 1 h in any case because of the age constraint for globular cluster stars, and this would push the intersection to higher n. As noted earlier, the velocity power spectrum constraint shown here is probably biased toward high by the non-) m linear e †ects described by Silberman et al (2001).…”
Section: Combining With Other Constraintsmentioning
confidence: 74%
“…The shape parameter constraint is usually compatible with the cluster mass function constraint, at least if one allows for the possibility that the error bar in equation (11) is somewhat too small. However, the velocity power spectrum always implies a higher Ñuctuation amplitude than the cluster mass function, and the two constraints are not consistent within their stated 1 p uncertainties for any combination of n, and h. A recent ) m , analysis by Silberman et al (2001) shows that the discrepancy is probably a result of nonlinear e †ects on the velocity power spectrum, and that correcting for these yields results closer to the cluster constraint. We therefore regard the cluster constraint as more reliable, and we retain the velocity power spectrum curve mainly as a reminder of other data that can be brought to bear on these questions.…”
Section: Combining With Other Constraintsmentioning
confidence: 97%
“…In order to minimise the influence of poorly understood non-linear effects a non-linear velocity dispersion component σPV is introduced into the diagonal elements of the covariance matrix (Silberman et al 2001). This nuisance parameter is marginalised over in the analysis.…”
Section: Greene 2006)mentioning
confidence: 99%